Tinjauan Yuridis Terhadap Gugatan Mantan Ketua Mahkamah Konstitusi di PTUN Jakarta atas Pemulihan Jabatan sebagai Ketua Mahkamah Konstitusi dalam Konteks Kompetensi/Kewenangan Pengadilan Tata Usaha Negara dalam Penyelesaian Sengketa Tata Usaha Negara - Karensia Payoh; Arman Tjoneng (CV Rewang Rencang, 2024)
The purpose of this article is to examine the lawsuit filed by former Chief Justice of the Constitutional Court, Anwar Usman, and the decision that will be made by the Administrative Court (PTUN) regarding the lawsuit. This research employs a normative juridical method, analyzing the application of doctrines, norms, and legal principles to address specific legal issues. Data is obtained from books, journals, and other legal literature through a literature study. Anwar Usman was dishonorably dismissed as Chief Justice of the Constitutional Court for ethical violations in adjudicating case number 90/PUU-XXI/2023, which allowed his nephew, Gibran Rakabuming, to run in the 2024 presidential election. Anwar subsequently filed a lawsuit with the PTUN Jakarta, requesting the annulment of Suhartoyo's appointment as Chief Justice of the Constitutional Court for the 2023-2028 term, as well as the restoration of his reputation and reinstatement to his position. This article will discuss the two main petitions in the lawsuit, arguing that the PTUN should not grant Anwar Usman's petition because the decision complies with the applicable laws and regulations.